(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2024)
This study discusses the tradition of letters in the kingdom of Bima, especially concerning giving enslaved people as gifts to accompany letters. The data for this study were taken from the manuscript bundle of bo’ (official royal records) during the reign of Sultan Abdul Kadim Muhammad Shah (1751–1773). Now, the manuscript is part of the collection of the Samparaja Cultural Museum, Bima, West Nusa Tenggara and is coded C.011 Bo. Within the manuscript bundle, we found 117 (out of a total of 548) letters discussing slaves and slavery in the Bima kingdom. We first used philological research methods, then these texts were analysed with historical records to obtain a complete understanding of slaves and slavery in the 18th century AD societal traditions. The results showed that slaves giving as a gift accompanying the letter was a symbol of respect for the recipient of the letter, which was following the Malay correspondence tradition. For local rulers, slaves were the most valuable treasure. Slaves were also a determinant of social status among the nobility in the past. This practice applies not only in Bima but throughout the Malay land and even Southeast Asia.